Radicalism Prevention Strategy: An Analysis of the Desa Siaga-Desa Damai Program - Irfan Fahmi Nooryadi; Ahmad G. Dohamid; Mitro Prihartoro; Rudy Sutanto; Yulia Febi Zita Ronika (PT FORMOSA CENDEKIA GLOBAL, 2024)
Radicalism is a significant threat to national and social stability in Indonesia. The Indonesian government, through the National Counterterrorism Agency (BNPT), has launched the Desa Siaga-Desa Damai Program to empower village communities in maintaining peace and preventing radicalism. The program is based on the great potential that village communities have in creating a conducive environment through education, training and active community participation. This study aims to evaluate the effectiveness of the Desa Siaga-Desa Damai Program in preventing the spread of radicalism at the village community level. Using radicalism prevention theory, social constructivism theory, and national security theory, this study analyzes various aspects of the program. The results show that the proactive approach and community empowerment used in the program are effective in reducing the potential for radicalism. Through training, coaching, and the use of information technology to spread counter-radicalism messages, the program succeeded in strengthening social cohesion and increasing community resilience against radical ideologies. In addition, the program is in line with Desa's SDGs goal 16, which is to create a society of peace and justice. In conclusion, the Desa Siaga-Desa Damai Program is an effective model in maintaining national security from the threat of radicalism by empowering village communities and improving their welfare.